Model of Social Reflection in the Teacher's Professional Activity - Haydarova Mehri (International Journal on Integrated Education, 2023)
The article reveals the content of the concepts of reflection, reflection model, types of reflection. The teacher's reflection is considered as an integral part of his professional activity. The characteristic of the model of the structure of reflection in the professional activity of the teacher– educator is carried out.